Recombinant Prolidase Activates EGFR-Dependent Cell Growth in an Experimental Model of Inflammation in HaCaT Keratinocytes. Implication for Wound Healing - Nizioł, Magdalena; Ościłowska, Ilona; Baszanowska, Weronika; Pałka, Jerzy; Besio, Roberta; Forlino, Antonella; Miltyk, Wojciech (Frontiers in Molecular Biosciences, 2022)
This study was conducted to investigate the proliferative capacity of recombinant human prolidase (rhPEPD) in a human model of inflammation induced by IL-1β in HaCaT keratinocytes. In this report, we provide evidence that IL-1β stimulates keratinocyte proliferation, and rhPEPD significantly augmented this process through activation of epidermal growth factor receptor (EGFR) and downstream signaling proteins as phosphorylated Akt, ERK1/2, and STAT3, which are implicated in keratinocyte migration, proliferation, and epithelialization during the wound healing process. Inhibition of PEPD-dependent EGFR signaling by gefitinib supported the finding. Moreover, during activation of EGFR in the presence of IL-1β the epithelial-to-mesenchymal transition (EMT) occurred via loss of E-cadherin and gain of N-cadherin. The phenomenon was accompanied by an increase in the activity of matrix metalloproteinase-9 (MMP-9), suggesting extracellular matrix (ECM) remodeling during the inflammatory process. MMP-9 activation may result from nuclear translocation of NF-κB through IKK-mediated IκBα degradation. Interestingly, some mutated variants of PEPD (rhPEPD-G448R, rhPEPD-231delY, and rhPEPD-E412K) evoked the ability to induce EGFR-dependent HaCaT cell proliferation. To the best of our knowledge, this is the first report on the cross-talk between PEPD and IL-1β in the process of keratinocyte proliferation. The data suggest that both enzymatically active and inactive rhPEPD may activate EGFR-dependent cell growth in an experimental model of inflammation in HaCaT keratinocytes and the knowledge may be useful for further approaches for therapy of wound healing disorders.